Maternal prenatal selenium levels and child risk of neurodevelopmental disorders: A prospective birth cohort study. Issue 12 (24th September 2021) - Lee, Ashley Sang Eun; Ji, Yuelong; Raghavan, Ramkripa; Wang, Guoying; Hong, Xiumei; Pearson, Colleen; Mirolli, Gabrielle; Bind, Eric; Steffens, Andrew; Mukherjee, Jhindan; Haltmeier, Douglas; Fan, Zhihua ( Tina); et al.
Abstract: Selenium (Se) is an essential trace element involved in various biological processes, including neurodevelopment. Available literature indicates that both Se deficiency and excess may be detrimental to health. It is also known that Se can cross the placenta from maternal to fetal circulation. To date, the role of maternal Se status in child long‐term neurodevelopment is largely unexplored. This study investigated the temporal and dose–response associations between maternal Se status and child risk of neurodevelopmental disorders including autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). It consisted of 1550 mother–infant dyads from the Boston Birth Cohort. Maternal red blood cell (RBC) Se levels were measured in samples collected within 72 h of delivery (biomarker of third trimester Se status). Pediatric neurodevelopmental diagnoses were obtained from electronic medical records. Data analyses showed that maternal RBC Se levels were positively associated with child risk of developing ASD, with an adjusted odds ratio of 1.49 for ASD (95% CI: 1.09, 2.02) per IQR increase in Se. There was also a positive association between maternal Se and ADHD (OR: 1.29; 95% CI: 1.04, 1.56, per IQR increase in Se). These associations remained robust even after adjusting for pertinent covariables; and there was no significant interaction between Se and these covariables. Our findings suggest that prenatal exposure to high maternal Se levels may adversely affect child neurodevelopment. Our findings warrant further investigation; if confirmed, optimizing maternal prenatal Se levels may be necessary to maximize its health benefits while preventing undue risk. Lay Summary: Selenium (Se) is an essential nutrient for the health of the pregnant mother and her baby. While Se can readily cross the placenta from maternal to fetal circulation, little is known about maternal Se status on her child's neurodevelopmental outcomes. We studied over 1500 mother–child dyads from birth to school age of the child. We found that babies born from mothers with high blood Se levels may be at increased risk of developing autism spectrum disorder or attention deficit hyperactivity disorder. Given this is the first study of the kind, more study is needed to confirm our findings.